Association between short-chain fatty acid intake and development of muscle strength loss among community-dwelling older Japanese adults - Rei Otsuka; Shu Zhang; Kanae Furuya; Chikako Tange; Giovanni Sala; Fujiko Ando; Hiroshi Shimokata; Yukiko Nishita; Hidenori Arai (Experimental Gerontology, 2023)
Background: Short-chain fatty acids (SCFAs) have been suggested to be associated with skeletal muscle mass maintenance. However, the role of dietary SCFAs in preserving muscle strength in the older population remains unclear. Objectives: To clarify the longitudinal association between the dietary intake of SCFAs and the development of low muscle strength in older community dwellers. Methods: Data were obtained from the National Institute for Longevity Sciences-Longitudinal Study of Aging cohort. The participants included 441 men and 382 women who participated in the baseline survey (the fifth wave, between 2006 and 2008) and at least one follow-up examination (sixth to ninth waves, between 2008 and 2022) and were ≥60 years old and did not have low muscle strength (defined as a grip strength of <28 kg for men and <18 kg for women) at baseline. Baseline nutrient intakes were assessed with a 3-day dietary record. A generalized estimating equation was employed to estimate the odds ratio (OR) and 95 % confidence intervals (CIs) for low muscle strength per 1 standard deviation (SD) increase in the intake of SCFAs and other nutrients at baseline (adjusted for sex, age, follow-up time, baseline grip strength, physical activity, smoking, family income, education, and disease histories). Results: The mean (SD) follow-up time and number were 7.8 (3.2) years and 3.2 (1.0) times, respectively. Approximately 8.1 % of the participants exhibited muscle strength loss in at least one follow-up assessment. The multivariate-adjusted OR (95 % CIs) was 0.77 (0.63–0.93) for each 1-SD increase in SCFA intake (268 mg/day), and the ORs for the highest through the lowest tertiles of SCFA intake were 1.00 (reference), 1.44 (0.95–2.17), and 1.83 (1.20–2.78), respectively (trend p = 0.005). The results remained significant after multivariate adjusting for energy or fat intake. Conclusion: Dietary intake of SCFAs may prevent muscle strength decline in community-dwelling older adults.